Functional Characterization of the Semisynthetic Bile Acid Derivative INT-767, a Dual Farnesoid X Receptor and TGR5 Agonist - Rizzo, Giovanni; Passeri, Daniela; De Franco, Francesca; Ciaccioli, Gianmario; Donadio, Loredana; Rizzo, Giorgia; Orlandi, Stefano; Sadeghpour, Bahman; Wang, Xiaoxin X.; Jiang, Tao; Levi, Moshe; Pruzanski, Mark; et al. (Molecular pharmacology, 2010)
Two dedicated receptors for bile acids (BAs) have been identified, the nuclear hormone receptor farnesoid X receptor (FXR) and the G protein-coupled receptor TGR5, which represent attractive targets for the treatment of metabolic and chronic liver diseases. Previous work characterized 6α-ethyl-3α,7α-dihydroxy-5β-cholan-24-oic acid (INT-747), a potent and selective FXR agonist, as well as 6α-ethyl-23(S)-methyl-3α,7α,12α-trihydroxy-5β-cholan-24-oic acid (INT-777), a potent and selective TGR5 agonist. Here we characterize 6α-ethyl-3α,7α,23-trihydroxy-24-nor-5β-cholan-23-sulfate sodium salt (INT-767), a novel semisynthetic 23-sulfate derivative of INT-747. INT-767 is a potent agonist for both FXR (mean EC50, 30 nM by PerkinElmer AlphaScreen assay) and TGR5 (mean EC50, 630 nM by time resolved-fluorescence resonance energy transfer), the first compound described so far to potently and selectively activate both BA receptors. INT-767 does not show cytotoxic effects in HepG2 cells, does not inhibit cytochrome P450 enzymes, is highly stable to phase I and II enzymatic modifications, and does not inhibit the human ether-a-go-go-related gene potassium channel. In line with its dual activity, INT-767 induces FXR-dependent lipid uptake by adipocytes, with the beneficial effect of shuttling lipids from central hepatic to peripheral fat storage, and promotes TGR5-dependent glucagon-like peptide-1 secretion by enteroendocrine cells, a validated target in the treatment of type 2 diabetes. Moreover, INT-767 treatment markedly decreases cholesterol and triglyceride levels in diabetic db/db mice and in mice rendered diabetic by streptozotocin administration. Collectively, these preclinical results indicate that INT-767 is a safe and effective modulator of FXR and TGR5-dependent pathways, suggesting potential clinical applications in the treatment of liver and metabolic diseases.